Protein disulfide isomerase ameliorates β-cell dysfunction in pancreatic islets overexpressing human islet amyloid polypeptide. (15th January 2016) - Montane, Joel; de Pablo, Sara; Obach, Mercè; Cadavez, Lisa; Castaño, Carlos; Alcarraz-Vizán, Gema; Visa, Montserrat; Rodríguez-Comas, Júlia; Parrizas, Marcelina; Servitja, Joan Marc; Novials, Anna
Abstract: Human islet amyloid polypeptide (hIAPP) is the major component of amyloid deposits in islets of type 2 diabetic patients. hIAPP misfolding and aggregation is one of the factors that may lead to β-cell dysfunction and death. Endogenous chaperones are described to be important for the folding and functioning of proteins. Here, we examine the effect of the endoplasmic reticulum chaperone protein disulfide isomerase (PDI) on β-cell dysfunction. Among other chaperones, PDI was found to interact with hIAPP in human islet lysates. Furthermore, intrinsically recovered PDI levels were able to restore the effect of high glucose- and palmitate-induced β-cell dysfunction by increasing 3.9-fold the glucose-stimulated insulin secretion levels and restoring insulin content up to basal control values. Additionally, PDI transduction decreased induced apoptosis by glucolipotoxic conditions. This approach could reveal a new therapeutic target and aid in the development of strategies to improve β-cell dysfunction in type 2 diabetic patients. Highlights: PDI interacts with hIAPP in human islet lysates. PDI overexpression restores β-cell function under glucolipotoxic conditions. PDI overexpression decreases apoptosis in glucolipotoxic conditions.